Chemistry for biologists - Fisher, J. [ (Julie)]; Arnold, J. R. P. [ (John R. P.)] (BIOS instant notes, 2013)
"Knowledge you need in an instant! BIOS Instant Notes in Chemistry for Biologists, Third Edition, is the perfect text for undergraduates looking for a concise introductionto the subject, or a study guide to use before examinations. Each topic begins with a summary of essential facts-an ideal revision checklist-followed by a description of the subject that focuses on core information, with clear, simple diagrams that are easy for students to understand and recall in essays and exams. BIOS Instant Notes in Chemistry for Biologists, Third Edition, is fully up-to-date and covers: The elements -- Chemical bonds and molecular shape -- Water- the biological solvent -- Carbon, the basis for life on Earth -- 3D-molecular structure of organic compounds -- Small inorganic molecules of biological importance -- Some metals in biology -- Molecular interactions -- Common reaction types of carbon based compounds -- Organic compounds by chemical class -- Aromatic compounds -- Chemical synthesis of biological molecules -- Important biological macromolecules by class -- Aqueous behaviour -- Elementary thermodynamics -- Kinetics -- Spectroscopy -- Appendix "-- Provided by publisher